Singapore investment in China : opportunities and risks - Ang, Geok Bee (2015)
The content of this project is mainly to examine the opportunities and risks of Singapore's investment in China and the effect on the Singapore economy. As the government has been encouraging Singaporeans to venture abroad, this project will help its readers to have an idea of the various types of investments and to understand the underlying risks. These two areas are important considerations for the potential investors while evaluating the viability of the possible investment projects in China. This topic on investment in China is very broad but much effort has been put in to cover as many areas as possible to give a comprehensive study within the limited time frame. Literature review as well as interviews are the main sources of collecting information, data and statistics. Opportunities of investment are abundant in the primary, secondary as well as the tertiary sectors of the Chinese economy. Foreign exchange risks, business risks and corruption risks are the more prominent risks that the investors should pay attention to in risks management. As good returns are always accompanied by high risks, it is vital that the investment projects are properly evaluated Successful investment projects would not only benefit Singapore companies and businesses but also contribute to the Singapore economic growth.